English Supervisors’ Perspectives of Supervision in Omani Public Schools - المحروقي، رحمة بنت ابراهيم; دينمان، كرستيان (جامعة السلطان قابوس - كلية الآداب والعلوم الاجتماعية, 2019)
The current study examined English supervisors’ perspectives of supervision in Omani public schools through the administration of a three-part, 13-category Likert-scale questionnaire. The questionnaire was distributed as part of a larger nation-wide investigation to 48 English supervisors in Omani schools and was completed by 35 participants. Areas examined included participants’ views of the supervisory process, including its effectiveness, supervisor roles and qualifications, challenges and opportunities for professional development, and the contributions supervision makes to teacher development. The questionnaire also explored participant engagement in a series of steps before, during, and after supervisor observation. Mixed attitudes about the supervisory process were reported, although a number of important concerns were raised about the way English supervision occurs in Omani government schools.
تتناول هذه الدراسة آراء مشرفي اللغة الإنجليزية حول الإشراف في المدارس الحكومية العمانية من خلال إجراء استبانة تتكون من ثلاثة أقسام تضم 13 فئة من مقياس ليكرت. وتم توزيع الاستبانة كجزء من استقصاء موسع لعدد 48 مشرف لغة إنجليزية على مستوى السلطنة وقد أكمله 35 مستجيبا، وشملت المجالات التي تناولها الاستقصاء آراء المشاركين عن العملية الإشرافية بما في ذلك فعاليتها، وأدوار المشرف ومؤهلاته، والتحديات والفرص من أجل التطوير المهني، وإسهامات المشرف حيال تطوير المعلم. كما تناولت الاستبانة إشراك المشرفين في سلسلة من الخطوات قبل وخلال وبعد القيام بعملية الإشراف. وقد خلصت الدراسة لمواقف متباينة حول العملية الإشرافية، رغم وجود عدد من النقاط التي تستدعي الاهتمام بشأن الإشراف التربوي في حصص اللغة الإنجليزية بالمدارس الحكومية العمانية.
Keywords: اللغة الانجليزية -- المؤسسات التعليمية -- سلطنة عمان -- الاشراف المدرسي